The Effect of Work Motivation and Quality of Work Life on Intention to Stay with Strengthening Organizational Commitment as a Mediation Variable : Study of BLUD Employees at the Madiun City Regional General Hospital (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine and analyze the influence of work motivation and Quality of Work Life on Intention to Stay, mediated by organizational commitment. The population in this study consisted of 162 employees of the Public Service Agency (BLUD) at the Madiun City Regional General Hospital. The sampling technique used was proportional random sampling to ensure representative data. Data were collected through structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software version 4.0. The results indicate that work motivation has a positive and significant effect on organizational commitment, while quality of work life also significantly enhances organizational commitment. Furthermore, organizational commitment significantly influences intention to stay. In addition, work motivation and quality of work life directly increase employees’ intention to stay. The mediation analysis shows that organizational commitment partially mediates the effect of work motivation and quality of work life on intention to stay. These findings highlight the importance of strengthening organizational commitment through improved motivation and quality of work life to retain employees in public healthcare institutions.